Combustion-driven synthesis route for bimetallic Ag–Bi nanoparticle-anchored carbon nanotube electrodes for high-performance supercapacitors. (15th October 2022) - Cha, Youngsun; Kim, Taewon; Seo, Byungseok; Choi, Wonjoon
Abstract: Bimetallic nanostructures within carbon-based materials can overcome the fundamental limits of energy materials, which cannot be obtained using a single material. However, their synthesis involves time-consuming and complex processes that cause phase/interface segregation and non-uniformly distributed metal elements. Herein, we report a facile combustion-driven synthesis for bimetallic Ag–Bi nanoparticle (NP)-anchored carbon nanotube (CNT) electrodes. One-step combustion wave passing through freestanding films comprising Ag2 O and Bi powders, nitrocellulose layers within CNTs enables high-density thermochemical reactions in seconds. The rapid heating-cooling rates induce the formation of liquefied Ag–Bi and trapping of metastable Ag–Bi phases at the carbon surfaces, thereby synthesizing homogeneously mixed bimetallic Ag–Bi NPs anchored on the CNTs, along with smaller diameters (∼20 nm) and high distribution density. A supercapacitor electrode employing them exhibits outstanding specific capacitance and retention (1372-1093 Fg -1 at 2-5 mVs −1, and 101.3% of the stabilized capacitance after 10, 000 cycles at 100 mVs −1 ). This was attributed to the large active site surface area from the small diameters and high distribution density of the bimetallic Ag–Bi NPs by low surface energy, and highly stable adhesion to the CNTs. The synthesis strategy can be extended to a scalable fabrication method of various multi-metallic nanostructures for versatile electrochemical electrodes and catalysts. Graphical abstract: Image 1